Labour productivity in the Hungarian agriculture - Bozsik, Norbert; Magda, Róbert (Acta Agraria Debreceniensis, 2018)
This paper presents the situation of the agricultural labour employment and evaluates the agricultural labour productivity in Hungary. Since Hungary’s EU accession, the share of agricultural employment in the total employed population has been stabilized at around 5% in the country. Due to low wages, low profit and low prestige, agricultural jobs are not attractive. The gross and net labour productivity gap between Hungary and the EU have been significant since the EU accession. The agricultural labour productivity of the Hungarian regions also shows a different picture. The labour productivity influences the cost, profitability and competitiveness of products. The advantage of the cheap labour force in Hungary’s agriculture significantly decreased due to low labour productivity. There are several opportunities to increase the agricultural labour productivity such as the increase of labour force qualification, moving toward producing higher value added agri-food products, rejuvenation of population in agriculture and the improvement of the conditions of financing agriculture.